2014
DOI: 10.1523/jneurosci.0159-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin Clusters Are Absent from Small Diameter Primary Afferent Terminals Despite the Presence of GABAA Receptors

Abstract: Whereas both GABA A receptors (GABA A Rs) and glycine receptors (GlyRs) play a role in control of dorsal horn neuron excitability, their relative contribution to inhibition of small diameter primary afferent terminals remains controversial. To address this, we designed an approach for quantitative analyses of the distribution of GABA A R-subunits, GlyR ␣1-subunit and their anchoring protein, gephyrin, on terminals of rat spinal sensory afferents identified by Calcitonin-Gene-Related-Peptide (CGRP) for peptider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 112 publications
4
68
0
Order By: Relevance
“…This is especially notable given that selective activation of GABA A receptors containing α2 and/or α3 is effective against neuropathic and inflammatory pain. 27 Lorenzo et al 24 showed that the α1 glycine receptor subunit was absent from those terminals, arguing against the involvement of glycine in presynaptic inhibition and pointing instead to GABA, consistent with the above results and with other physiological evidence. 28 GABA B receptors are metabotropic receptors whose activation leads, amongst other things, to activation of potassium channels via G-proteins.…”
Section: Gaba and Glycine Receptorssupporting
confidence: 85%
See 1 more Smart Citation
“…This is especially notable given that selective activation of GABA A receptors containing α2 and/or α3 is effective against neuropathic and inflammatory pain. 27 Lorenzo et al 24 showed that the α1 glycine receptor subunit was absent from those terminals, arguing against the involvement of glycine in presynaptic inhibition and pointing instead to GABA, consistent with the above results and with other physiological evidence. 28 GABA B receptors are metabotropic receptors whose activation leads, amongst other things, to activation of potassium channels via G-proteins.…”
Section: Gaba and Glycine Receptorssupporting
confidence: 85%
“…Recent work has shown that the terminals of both peptidergic and nonpeptidergic C fibers lack gephyrin. 24 This suggests a more diffuse GABA A receptor distribution although gephyrin-independent clustering of α2 GABA receptor subunits is possible 25 and α2 subunits are predominant presynaptically. 26 Selective deletion of the α2 GABA receptor subunit from nociceptive primary afferents significantly reduced the antihyperalgesic effects of spinal diazepam.…”
Section: Gaba and Glycine Receptorsmentioning
confidence: 99%
“…α5 ) α1. The GABA A R subtype-dependence of spinal antihyperalgesia hence matched well with the expression of the different α subunits in the superficial dorsal horn (Bohlhalter, Weinmann, M€ ohler, & Fritschy, 1996;Lorenzo et al, 2014;Paul, Zeilhofer, & Fritschy, 2012).…”
Section: Spinal Gaba a R Subtypes Mediating Antihyperalgesia: Evidencsupporting
confidence: 57%
“…Axo-axonic contacts have also been found in nociceptor terminals, but less frequently than in terminals of non-nociceptive fibers (Alvarez, Kavookjian, & Light, 1993;Ribeiro-Da-Silva, Castro-Lopes, & Coimbra, 1986;Ribeiro-da-Silva, Tagari, & Cuello, 1989). Two recent studies disagree on the presence of gephyrin clusters on nociceptor terminals (Lorenzo et al, 2014;Paul et al, 2012). Because gephyrin is required for postsynaptic clustering of inhibitory neurotransmitter receptors in central neurons, the presence or absence of gephyrin clusters from sensory fiber terminals may be taken as an argument in favor or against the presence of axo-axonic synapses between GABAergic interneurons and nociceptor terminals.…”
Section: Mechanisms Of Presynaptic Inhibitionmentioning
confidence: 99%
“…Taken together, our results are consistent with the model that sensory afferents receive primarily GABAergic inputs (likely through axo-axonic synapses) and some extrasynaptic glutamatergic inputs from local interneurons in the spinal cord ( Figure 7B). Some of the GABAergic interneurons coexpress glycine, but since DRG neurons do not express glycine receptor (64), glycine released from these neurons is unlikely to modulate primary afferents. RVM-derived dual GABAergic/enkephalinergic inputs onto primary afferents have antinociceptive functions.…”
Section: Discussionmentioning
confidence: 99%